Overexpression of PTPRN Promotes Metastasis of Lung Adenocarcinoma and Suppresses NK Cell Cytotoxicity - Song, Xinyue; Jiao, Xue; Yan, Han; Yu, Lifeng; Jiang, Longyang; Zhang, Ming; Chen, Lianze; Ju, Mingyi; Wang, Lin; Wei, Qian; Zhao, Lin; Wei, Minjie (Frontiers in Cell and Developmental Biology, 2021)
Background: Lung adenocarcinoma (LUAD) is the most common diagnostic histologic subtype of non-small cell lung cancer (NSCLC), but the role of receptor-type tyrosine-protein phosphatase-like N (PTPRN) in LUAD has not been studied. Methods: We conducted a bioinformatic analysis to identify the expression of PTPRN on LUAD data from the Cancer Genome Atlas (TCGA) and the relationship between PTPRN and overall survival of LUAD patients. The effects of PTPRN on the migration ability of LUAD cells and the underlying mechanisms were investigated by in vitro and in vivo assays (i.e., wound healing assay, transwell assay, western blotting, xenograft model and immunohistochemistry). GSEA and CIBERSORTx were used to analyse the correlation between PTPRN and different tumor-infiltrating immune cells. LDH assay and ELISA assay were conducted to examine natural killer (NK) cells cytotoxicity. Results: In our study, we found that PTPRN was up-regulated in LUAD and related to metastasis of LUAD patients. Besides, PTPRN was correlated with poor prognosis in TCGA-LUAD dataset. PTPRN overexpression promoted LUAD cell migration and the expression of EMT markers by influencing MEK/ERK and PI3K/AKT signaling. Moreover, PTPRN expression was significantly associated with tumor-infiltrating immune cells, especially NK cells. A549 and H1299 cells over-expressed PTPRN inhibited NK cells cytotoxicity. Conclusions: Taken together, these findings demonstrated that PTPRN might be a potential and novel therapeutic target modulating anti-tumor immune response in treatment of LUAD.